2012
DOI: 10.1177/2047487312449414
|View full text |Cite
|
Sign up to set email alerts
|

Optimal type 2 diabetes mellitus management: the randomised controlled OPTIMISE benchmarking study: baseline results from six European countries

Abstract: OPTIMISE confirms that target achievement in the primary care setting is suboptimal for all three critical quality indicators. This represents an unmet but modifiable need to revisit the mechanisms and management of improving care in type 2 diabetes. OPTIMISE will help to assess whether benchmarking is a useful clinical tool for improving outcomes in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 61 publications
(60 reference statements)
3
17
0
1
Order By: Relevance
“…These drugs target various facets of metabolic pathways involved in the pathophysiology of the disease [1]. Despite this, fewer than 50 % of the patients achieve glycemic treatment goals predefined by expert societies [2][3][4]. Additionally, concerns such as progressive deterioration of b-cell function, weight gain, and hypoglycemia limit the clinical utility of some of these drugs.…”
Section: Introductionmentioning
confidence: 99%
“…These drugs target various facets of metabolic pathways involved in the pathophysiology of the disease [1]. Despite this, fewer than 50 % of the patients achieve glycemic treatment goals predefined by expert societies [2][3][4]. Additionally, concerns such as progressive deterioration of b-cell function, weight gain, and hypoglycemia limit the clinical utility of some of these drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Los hallazgos más saltantes en un estudio canadiense (26) muestran que, a pesar de que la mayoría de sus pacientes era diabético y tenía factores de riesgo cardiovascular, solo 46% recibía bloqueadores del sistema renina angiotensina aldosterona y solo 32% tomaba estatinas. En el estudio de Kanter (27) , 71% tenía HTA y aunque 32,4% sufría de dislipidemia, solo 22,4% recibía estatinas.…”
Section: Discussionunclassified
“…A reduction in glycated hemoglobin (HbA1c) remains the cornerstone of diabetes management [2] and until recently the HbA1c goal in most T2D patients was <7% [3]. However, observational studies in various groups of patients with T2D reported that attaining the HbA1c target remained unsatisfactory [4][5][6][7], although an improvement in the percentage of patients at target from 1999 through 2010 was shown in one study [8]. One of the main barriers in maintaining long-term glycemic control in T2D is the progressive nature of the disease attributed to a continuous decline in beta-cell function [9] and many patients require insulin after a number of years since diagnosis [10].…”
Section: Background and Aimsmentioning
confidence: 99%